Sahodaran Ayyappan : towards a democratic future life and select works - Sekhar, Ajay, 1976-; Ayyappan, Ke., 1889-1968 (Calicut : Other Books, 2012)
Biography and selected works of Ke. Ayyappan, 1889-1968, social ref ormer cum poet from Kerala.
Includes bibliographical references (p. 260-262) and index.
Keywords: Ayyappan, Ke., -- 1889-1968.; Social reformers; Authors, Malayalam -- 20th century -- Biography